Progress in piezotronic and piezo-phototronic effect of 2D materials. (7th September 2018) - Peng, Yiyao; Que, Miaoling; Tao, Juan; Wang, Xiandi; Lu, Junfeng; Hu, Guofeng; Wan, Bensong; Xu, Qian; Pan, Caofeng
Abstract: Two-dimensional (2D) materials, possessing numerous remarkable properties including high electrical conductivity, optical transparency and mechanical strength, have supplied a fertile soil for theoretical research and practical application in electronics and optoelectronics. Due to a persistent need of strain sensors, microelectromechnical system (MEMS), nanorobots and active flexible electronics, piezotronic and piezo-phototronic effect of 2D materials have been attracting growing attentions in latest years. Therefore, a comprehensive and intensive understanding of piezotronic and piezo-phototronic effect of 2D materials is required. Here we review the recent progress in theoretical analysis and experimental observation of piezotronic and piezo-phototronic effect of 2D materials enabled by non-centrosymmetric crystal structure. After introducing the fundamental physics of piezotronic and piezo-phototronic effect concisely, the origination and analysis of the piezoelectricity in 2D materials are discussed in detail. Furthermore, we focus on the application in piezotronic and piezo-phototronic effect of transition-metal dichalcogenides (TMDCs) including transistor, nanogenerator, humidity sensor and photodetector. Moreover, some other 2D piezoelectric materials (PEMs) are also been summarized owing to their potential applications in piezotronics and piezo-phtotronics. Finally, some perspectives are put forward on the following opportunities and challenges for future research in this emerging field.